Monolithic anion-exchange chromatography yields rhinovirus of high purity. - Allmaier, G; Blaas, D; Bliem, C; Dechat, T; Fedosyuk, S; Gösler, I; Kowalski, H; Weiss, V (Elsevier, 2017)
For vaccine development, 3D-structure determination, direct fluorescent labelling, and numerous other studies, homogeneous virus preparations of high purity are essential. Working with human rhinoviruses (RVs), members of the picornavirus family and the main cause of generally mild respiratory infections, we noticed that our routine preparations appeared highly pure on analysis by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), exclusively showing the four viral capsid proteins (VPs). However, the preparations turned out to contain substantial amounts of contaminating material when analyzed by orthogonal analytical methods including capillary zone electrophoresis, nano electrospray gas-phase electrophoretic mobility molecular analysis (nES GEMMA), and negative stain transmission electron microscopy (TEM). Because these latter analyses are not routine to many laboratories, the above contaminations might remain unnoticed and skew experimental results. By using human rhinovirus serotype A2 (RV-A2) as example we report monolithic anion-exchange chromatography (AEX) as a last polishing step in the purification and demonstrate that it yields infective, highly pure, virus (RV-A2 in the respective fractions was confirmed by peptide mass fingerprinting) devoid of foreign material as judged by the above criteria.